Tradition as a basis for the formation of political culture of china - Kaskarauova А. (Journal of Oriental Studies, 2016)
This article examines the ideological line of the current leadership, which is caused by a combination of modern culture and the finest achievements of traditional Chinese culture. Analyze the influence of the ancient traditions of China’s current model of China’s modernization.